Iron Deficiency among Patients with Febrile Seizures in Al Ramadi Maternity and Children teaching Hospital, Western Iraq - Sahar j. AL- Hiali (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background : Febrile seizures are the most predominant neurological disorders in children between 6 months-5 years, at the same time iron deficiency anemia is one of nutritional insult that implicated as risk factor for occurrence of febrile seizures. Objectives: to estimate the role of iron deficiency as a risk factor for febrile seizures in children aged 6 months -5 years, western Iraq. Patients and method:- A case control study has been conducted in AL Ramadi maternity and children teaching hospital during January to October of 2016. All children with history of febrile seizures aged 6 months-5years were involved as cases group, others with febrile illness and no seizures were considered as control group. Data from 58 child of each group were collected. The data include age, sex ,temperature, causes of febrile illness, Hb ,hematocrit and s. ferritin levels. The data were subjected to statistical analysis run under IBM SPSS ver. 23. Results:- Means age ± SD were 27.48±14.83 & 23.24±14.37 months in cases and control groups respectively with no significant difference between them. Most of the children (65.52%) of those with febrile seizures were less than 3 years old. Mean temperature of cases group (38.860 C) was found to be significantly greater than that of the control group (38.520 C) at p-value <0.01. Mean Hb level ,PCV%, s. ferritin level were significantly lower in cases group than in control group. Proportion of iron deficiency anemia was significantly higher in febrile seizure group (65.52%) than in control group (31.03%) at p-value< 0.01. Conclusions: Occurrence of IDA in cases group is found to be more than 2 times of that in the control group. Early detection and proper treatment of IDA can play a prominent role in limitation the prevalence of febrile seizures among children below 5 years.